Cultura organizacional, recursos humanos e a sustentabilidade: o papel estratégico da gestão de pessoas no Instituto Federal de Santa Catarina – Campus Jaraguá do Sul - Centro - Raulino, Carlos Eduardo (2020)
We live in constant changes and consequently the need to improve our lives leads us to think and act sustainably, whether at home or at work. Higher Education Institutions as producers and disseminators of knowledge, responsible for forming opinions, should promote the debate about sustainability. Brazilian public institutions must adhere to this sustainable footprint and build their Sustainable Logistics Plans - PGLS as established by law, in order to encourage the development of a sustainable culture. And, in terms of organizational culture, the People Management sector should strategically seek to develop practical actions for this. In this context, the question arose: What initiatives can be pursued in order to highlight a change in the organizational culture through strategic People Management with regard to sustainability? The general objective of this research was to analyze the IFSC Sustainable Program at IFSC's Jaraguá do Sul Campus, based on federal legislation and in light of the United Nations Sustainable Development Goals. To assist, the program was studied, as well as other legislation, the program was described in the light of the SDGs and finally, practical actions were proposed to encourage the rescue of the sustainable IFSC at the Jaraguá do Sul Campus - IFSC Center. To achieve this objective, of a descriptive nature, it was guided by the qualitative methodology and used the case study procedure, where the structured interviews with the PGLS, the legislation and the theory were triangulated. After the content analysis, indicated by Bardin (2016), it was possible to understand that, from the perspective of the interviewees, in addition to the institution's flawed communication process, there is a need to work with human resources so that they realize the importance of sustainability in the IFSC. In addition to encouraging employees through initial and continuing training, the institution should create conditions for the People Management sector to act in channeling efforts and in building values from the awareness and training of employees from the perspective of PGLS.